Laying the ghost of the relativistic temperature transformation - Landsberg, P. T.; Matsas, GEA (Elsevier B.V., 1996)
Using the Unruh-DeWitt detector, it is shown that a universal and continuous Lorentz transformation of temperature cannot exist for black-body radiation. Since any valid Lorentz transformation of temperature must be able to deal with black-body radiation, it is concluded that a universal and continuous temperature transformation does not exist.